As dificuldades da prática docente no processo de alfabetização e letramento numa escola do campo do município de Abaetetuba/PA - SILVA, Izaneide Brandão da (2023)
The objective of this research is to analyze the difficulties in the teaching practice in the literacyand literacy process in a multigrade class at the Cristo Redentor school located in the countryside. This research arises from the problem: What are the teaching difficulties in the literacy and literacy process in a multigrade class at Cristo Redentor school? The research is ofa qualitative nature and was carried out in a municipal school in a multigrade class of 2nd and 3rd year. The data collection instruments were observation, carried out in the school context, semi-structured interview carried out with the teacher of that class. With the material collected, we performed a content analysis. The results indicate that the difficulty in the literacy stage in relation to reading and writing is to associate letters in syllables and words and that classroom practices are traditional, one of the greatest challenges to obtain positive results in the face of student development. being literate and literate is the lack of qualified training and the lack of interest in developing attractive methods, showing a certain resistance from the teacher in changing from old methods to current and playful ones.